2006
DOI: 10.1080/00498250600700496
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cytostatically active 6-aminobenzo[c]phenanthridines by human and porcine hepatic microsomes and recombinant cytochrome P450 enzymes

Abstract: A new and convenient two-step synthesis of 11-substituted 6-amino-11,12-dihydrobenzo[c]phenanthridines and 6-aminobenzo[c]phenanthridines (BPs and BP-Ds) was developed recently in the authors' laboratory. These compounds revealed a high antitumoral activity in in vitro and in vivo test systems. In particular, 11-phenyl-substituted derivatives with two or three methoxy groups showed good activity. It was not clear if the dihydro-derivatives (BPs) were transformed enzymatically into the phenanthridines (BP-Ds), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The substituent at position 6 can be completely removed by reduction of the thione, leading to structures 26 and 27 (BPE and BP‐DE series) with the e liminated substituent. For a few examples, we showed that alternatively the oxo group can be transformed into the chlorine substituent, which allowed introduction of the hydroxylamine group at position 6, for example . More specialized transformations included formation of the benzo[ c ]phenanthridine skeleton, which means a phenanthridine bearing a proton at position 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substituent at position 6 can be completely removed by reduction of the thione, leading to structures 26 and 27 (BPE and BP‐DE series) with the e liminated substituent. For a few examples, we showed that alternatively the oxo group can be transformed into the chlorine substituent, which allowed introduction of the hydroxylamine group at position 6, for example . More specialized transformations included formation of the benzo[ c ]phenanthridine skeleton, which means a phenanthridine bearing a proton at position 11.…”
Section: Resultsmentioning
confidence: 99%
“…For af ew examples, we showed that alternatively the oxo group can be transformed into the chlorine substituent,w hich allowed introduction of the hydroxylamine group at position 6, for example. [14] More specialized transformations included formation of the benzo[c]phenanthridine skeleton, which meansaphenanthridine bearing ap rotona t position1 1. This structure is accessible by using formaldehyde as startingm aterialw ith subsequento xidation and cleavage of the substituent at position6.…”
Section: Furthersyntheticm Odificationsmentioning
confidence: 99%